PENGEMBANGAN BUKU AJAR MATA KULIAH PENDIDIKAN IPS UNTUK PGMI MENGGUNAKAN EXPANDING COMMUNITY APPROACH - M. Irfan Islamy (STAI Ma'had Aly Al-Hikam Malang, 2019)
This research is a continuation of the research on the Development of Textbooks for Social Studies Courses with the 2013 Curriculum Based Concept Approach. Development with Expanding Community Approach is used to create a hierarchical material that starts from a simple concept to a broader concept while paying attention to the distribution of Social Studies material at the level of Elementary School based on the 2013 Curriculum. Research & development of textbooks for social studies education MI / SD with Expanding Community Approach aims to develop social studies textbooks in the Elementary School Teacher Education department that can be used as learning resources for students in Social Studies courses. This development research uses the Thiarajagan 4-D model with the steps of Define, Design, Develop, and restrictions on Desseminate. Research on the development of Social Studies course textbooks for Elementary School Teacher Education with Expanding Community Approach received a very decent category with a score of 81% from material experts, a decent category with a score of 80% from linguists, and a very decent category with a score of 87% from design experts. The data can provide the conclusion that the textbooks of Social Studies courses using the expanding community approach are categorized as feasible.